Ultrathin high-flexibility vapor chamber and intelligent glasses
By adopting ultra-thin and highly flexible heat-smoothing plates and using the combination of ultra-elastic foil and liquid-absorbing core structures, the problem of the existing heat-smoothing plate failing after repeated bending is solved, and efficient heat dissipation and long-term under bending conditions are achieved life.
Patent Information
- Application Number
- CN202411533272.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-30
- Publication Date
- 2025-02-11
AI Technical Summary
The existing heat-smoothing plates are prone to failure after repeated bending, and cannot effectively solve the heat dissipation needs of the rotating joint parts of electronic products.
It uses ultra-thin and highly flexible heat-smoothing plate, and its shell is made of ultra-elastic foil with an elastic limit of 6% to 10%, and an elastic modulus of less than or equal to 150Gpa. It combines the liquid absorbent core structure and the gas-liquid of liquid working fluid. The phase change principle enables rapid heat dissipation and ensures that the material is kept in the elastic deformation zone when bending.
It achieves efficient heat dissipation under repeated bending, and the bending life can reach tens of thousands to tens of thousands of times, avoiding the problem of failure of the heat-smoothing plate due to repeated bending of small angles.
Smart Images

Figure CN119421383A_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 202210757800.2. The application date of the invention patent application 202210757800.2 is June 30, 2022, and the name of the invention is “A kind of smart glasses”. Technical Field
[0002] The present invention belongs to the technical field of electronic products, and in particular relates to an ultra-thin high-flexibility heat spreader and smart glasses. Background Art
[0003] With the rapid development of technology, smart glasses, notebooks, foldable phones and other electronic products are developing towards more compact, more powerful and more diversified functions. The core electronic components are developing towards more miniaturization, integration and higher performance. Although the space occupied is reduced, the power is greater and the heat generated is increased. Since heat has a great impact on the performance of electronic products and the use of users, existing electronic products mainly dissipate heat by setting up a heat spreader, which is a high thermal conductivity device that can quickly conduct the heat generated by electronic components in a small space.
[0004] At present, heat spreaders are mainly used for heat dissipation at the rotating joints of many electronic products such as smart glasses, notebooks, and folding mobile phones. However, most existing heat spreaders are rigid and easily break and fail after multiple bending, making them unsuitable for use in the rotating joints of electronic products.
[0005] In view of this, how to achieve rapid heat dissipation of the heat spreader and prevent failure due to repeated bending is an urgent problem to be solved. Summary of the invention
[0006] The purpose of the present invention is to provide an ultra-thin and highly flexible vapor chamber and smart glasses, aiming to solve the problem that the existing vapor chamber is prone to repeated bending and failure.
[0007] The present invention discloses an ultra-thin high-flexibility vapor chamber, the ultra-thin high-flexibility vapor chamber comprising:
[0008] A shell, wherein the shell is arranged to form a closed cavity, and opposite sides of the shell respectively form an evaporation side and a condensation side, and the shell is made of a superelastic foil with an elastic limit of 6% to 10% and an elastic modulus of less than or equal to 150 GPa, and the thickness of the superelastic foil is 10 um to 250 um;
[0009] A wick structure connected between the evaporation side and the condensation side and capable of forming a reflux path between the evaporation side and the condensation side;
[0010] And a liquid working medium is filled in the closed cavity and absorbed by the liquid wick structure, and the heat conducted to the evaporation side is conducted to the condensation side for heat dissipation by utilizing the heat dissipation principle of the gas-liquid two-phase change of the liquid working medium.
[0011] As an improvement, the superelastic foil is made of a titanium-nickel alloy, in which the atomic percentage of titanium and nickel elements is greater than or equal to 40%, and the total atomic percentage of the remaining elements is less than or equal to 10%; and the total atomic percentage of all elements in the titanium-nickel alloy is 100%.
[0012] As a refinement, the remaining elements include one or more of copper, iron, niobium and zirconium.
[0013] As an improvement, the titanium-nickel alloy is TiNi50 alloy, TiNiBb alloy or TiNi49Zr1 alloy.
[0014] As an improvement, the overall thickness of the ultra-thin high-flexibility vapor chamber is less than or equal to 1 mm.
[0015] As an improvement, the liquid absorbent core structure includes a first liquid absorbent core portion arranged on the inner side wall of the shell on the evaporation side, and a second liquid absorbent core portion arranged on the inner side wall of the shell on the condensation side, and a steam chamber is formed between the first liquid absorbent core portion and the second liquid absorbent core portion.
[0016] As an improvement, the first liquid absorbent core is attached to the inner wall of the shell on the evaporation side, and the second liquid absorbent core is attached to the inner wall of the shell on the condensation side. The first liquid absorbent core and the second liquid absorbent core are porous plastic, porous polymer, porous metal or multi-layer woven wire mesh; or, the first liquid absorbent core and the shell on the evaporation side are an integrally formed structure, and the second liquid absorbent core and the shell on the condensation side are an integrally formed structure.
[0017] As an improvement, an elastic buffer energy absorbing layer or a groove structure is provided on the condensation side and the evaporation side respectively.
[0018] As an improvement, the sealed chamber is configured as a negative pressure chamber.
[0019] As an improvement, the shell includes a first side cover structure and a second side cover structure that are snapped together, and the closed cavity is enclosed between the first side cover structure and the second side cover structure. The cover surface of the first side cover structure forms the condensation side, and the cover surface of the second side cover structure forms the evaporation side.
[0020] As an improvement, the ultra-thin high-flexibility heat spreader also includes a plurality of support structures spaced apart inside the closed cavity, each of the support structures is supported between the evaporation side and the condensation side, and a steam channel is formed between two adjacent support structures.
[0021] As an improvement, in the bent state, a bent portion is formed in the shell portion between two adjacent support structures, and the distance between the two adjacent support structures corresponding to the bent portion gradually decreases from the condensation side to the evaporation side.
[0022] The present invention also discloses a pair of smart glasses, which include the ultra-thin and highly flexible heat spreader.
[0023] Due to the adoption of the above technical solution, the beneficial effects achieved are as follows:
[0024] The ultra-thin and highly flexible heat spreader in the present invention comprises a shell, which is surrounded to form a closed cavity, and the two opposite sides of the shell respectively form an evaporation side and a condensation side, and the shell is made of a superelastic foil with an elastic limit of 6% to 10% and an elastic modulus of less than or equal to 150Gpa, and the thickness of the superelastic foil is 10um to 250um; a liquid wick structure, which is connected between the evaporation side and the condensation side and can form a reflux path between the evaporation side and the condensation side; and a liquid working medium, which is filled in the closed cavity and absorbed by the liquid wick structure, and the heat transferred to the evaporation side is transferred to the condensation side for heat dissipation by utilizing the heat dissipation principle of the liquid working medium undergoing a gas-liquid two-phase change. The smart glasses in the present invention comprise an ultra-thin and highly flexible heat spreader.
[0025] During installation, place the evaporation side of the ultra-thin, highly flexible vapor chamber against the heat source. Figure 1 The heat is conducted in the direction of the middle arrow A to the evaporation side of the ultra-thin high-flexibility heat spreader, and then from the evaporation side to the inside of the closed chamber. The liquid working medium inside the liquid wick structure 20 corresponding to the evaporation side absorbs heat and quickly vaporizes, taking away a large amount of heat at the same time. The heat of the steam diffuses from the high-pressure area to the low-pressure area inside the closed chamber. When the steam contacts the condensation side with a lower temperature, it will quickly condense into liquid and release heat energy. The liquid working medium condensed into liquid returns to the heat source under the action of the capillary force generated by the microstructure of the liquid wick structure, thereby completing a heat conduction cycle, using the liquid working medium The heat dissipation principle of gas-liquid two-phase change conducts the heat conducted to the evaporation side to the condensation side for heat dissipation; at the same time, the ultra-thin and highly flexible heat spreader made of super elastic foil with an elastic limit of 6% to 10% and an elastic modulus less than or equal to 150Gpa can not only quickly conduct the heat generated by the heat source, but also the test shows that the ultra-thin and highly flexible heat spreader is always in the elastic deformation zone of the material when repeatedly bent, and the bending life can reach tens of thousands to hundreds of thousands of times. It is not easy to fail due to repeated bending at small angles, which solves the problem that the existing heat spreader is prone to failure due to repeated bending. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a schematic cross-sectional structural diagram of an ultra-thin and highly flexible vapor chamber according to an embodiment of the present invention;
[0027] Figure 2 is a schematic cross-sectional structural diagram of an ultra-thin high-flexibility vapor chamber in a bent state according to an embodiment of the present invention;
[0028] Figure 3 It is the mechanical model of the material when it is bent and deformed;
[0029] In the figure: 11, first side cover structure; 12, second side cover structure; 13, bending part; 20, absorbent core structure; 21, first absorbent core part; 22, second absorbent core part; 30, supporting structure. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the embodiments described in the present invention are only for the convenience of simplifying the description and cannot be understood as limiting the present invention.
[0031] Figures 1 to 3 is a schematic diagram of the structure of an ultra-thin high-flexibility vapor chamber according to an embodiment of the present invention, wherein: Figure 1 FIG. 4 is a schematic cross-sectional view of an ultra-thin high-flexibility vapor chamber according to an embodiment of the present invention. Figure 2 The cross-sectional structure schematic diagram shows the bending state of the ultra-thin high-flexibility vapor chamber according to an embodiment of the present invention, Figure 3 The mechanical model of the material bending deformation is shown. For the convenience of description, only the part related to the present invention is shown in the figure.
[0032] It should be noted that if the directional indications involved in the present invention (such as up, down, front, back, etc.) are only used to explain the relative position relationship between the components in a certain specific posture, if the specific posture changes, the directional indication will also change accordingly; if the descriptions of "first", "second", etc. are involved in the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.
[0033] Depend on Figure 1 , Figure 2 and Figure 3 It can be seen that the ultra-thin high-flexibility vapor chamber of the embodiment of the present invention comprises:
[0034] A shell, the shell is arranged to form a closed cavity, and the two opposite sides of the shell form an evaporation side and a condensation side respectively. The shell is made of a superelastic foil with an elastic limit of 6% to 10% and an elastic modulus of less than or equal to 150Gpa. The thickness of the superelastic foil is 10um to 250um (i.e., the wall thickness of the shell), and the strength is greater than or equal to 700Mpa. The martensitic phase transition point of the superelastic foil is lower than -20°C, and the material shows good recoverable superelastic deformation at -20°C to 100°C; preferably, the thickness of the superelastic foil is 100um to 200um, which improves the hardness of the shell while maintaining elasticity;
[0035] The liquid wick structure 20 is connected between the evaporation side and the condensation side, and can form a reflux path between the evaporation side and the condensation side for the liquid working medium to reflux from the condensation side to the evaporation side;
[0036] The liquid working medium is filled in the closed cavity and absorbed by the liquid wick structure 20. The heat (such as Figure 1 The heat is conducted to the condensation side (as shown by the arrow A in the middle) for heat dissipation (as shown by the arrow A in the middle Figure 1 Usually, common liquid working fluids include pure water, ammonia, acetone and other liquid fluids, with a filling rate of 80%. Among them, water has the largest latent heat of evaporation and is the cheapest. It is easy to boil under low pressure and quickly take away a large amount of heat. It is the most common working fluid.
[0037] During installation, place the evaporation side of the ultra-thin, highly flexible vapor chamber against the heat source. Figure 1 The direction of the middle arrow A is conducted to the evaporation side of the ultra-thin high-flexibility heat spreader, and then conducted from the evaporation side to the inside of the closed cavity. The liquid working medium in the liquid wick structure 20 corresponding to the evaporation side absorbs heat and quickly vaporizes, taking away a large amount of heat at the same time. The heat of the steam in the closed cavity diffuses from the high-pressure area to the low-pressure area (i.e., the low-temperature area). Figure 1 In the direction of arrow B, when the steam contacts the condensation side with a lower temperature, it will quickly condense into liquid and release heat energy. The condensed liquid working medium returns to the heat source under the action of the capillary force generated by the microstructure of the liquid wick structure 20, as shown in FIG. Figure 1 The direction of arrows C1 and C2 in the middle completes a heat conduction cycle, and the heat (such as Figure 1 The heat is conducted to the condensation side (as shown by the arrow A in the middle) for heat dissipation (as shown by the arrow A in the middle Figure 1 (as indicated by arrow D in the middle).
[0038] In order to facilitate a clear understanding of the technical solution and technical effects of this embodiment, the principles on which the research and development design of this embodiment is based are described as follows:
[0039] When a material is bent and deformed, elastic deformation occurs first. After the external force is removed, the deformation of the material can be completely recovered. When the strain exceeds the elastic deformation limit of the material, plastic deformation will occur. Plastic deformation is irreversible. When the material is bent multiple times to produce plastic deformation, the plastic deformation will accumulate. When the accumulated plastic deformation exceeds the plastic limit of the material, the material will break and fail. For the heat spreader, the shell seal will break and the heat spreader will fail. For the wick structure, the capillary pores will close or the capillary wick will break, the power of the heat spreader will drop, and the heat dissipation capacity will be extremely reduced.
[0040] If you want a material to bend and deform tens of thousands of times without failure, a feasible design is to keep the material in the elastic deformation zone during repeated bending. For example, when a metal material is always in the elastic deformation zone, its fatigue bending life can reach hundreds of thousands of times, and its service life can reach more than ten years; once the material yields and enters the plastic deformation zone, due to the limited elongation of the material, the material will inevitably break after multiple bendings.
[0041] Therefore, when designing an ultra-thin and highly flexible heat spreader, the bending deformation (i.e., strain) of the material used to make the ultra-thin and highly flexible heat spreader can be always controlled within the elastic deformation limit of the material, thereby ensuring the heat dissipation effect while increasing its bending service life.
[0042] Figure 3 The figure shows the mechanical model of the material when it is bent and deformed. The thickness of the material is H, the bending radius is R, and the bending angle is θ. When the material is bent, the material on the outside suffers the greatest tensile deformation, and the tensile deformation becomes smaller as it goes deeper into the material. The dotted line in the middle indicates the neutral layer, that is, the deformation-free layer that is neither stretched nor compressed. Within it, the inner side of the material suffers symmetrical compression deformation, and the innermost material suffers the greatest compression deformation; therefore, the maximum tensile or compression deformation suffered by the material can be calculated.
[0043] The outermost length of the material is (R+H)θ, and the length of the neutral layer is (R+H / 2)θ. The maximum strain of the material is: [(R+H)θ-(R+H / 2)θ)] / (R+H / 2)θ=H / (2R+H). By substituting different bending radii R and foil thicknesses, the strain value of the material can be obtained, as shown in Table 1 below.
[0044] Table 1 Corresponding strains of foils of different thicknesses at different bending radii
[0045]
[0046] Table 2 Elastic modulus and elastic limit of common materials
[0047] Material Elastic modulus(GPa) Elastic limit (%) Copper Alloy ~105 <0.6 Stainless steel ~210 <1 aluminum ~77 <0.5 Titanium Alloy ~102 <2 nylon 3 <2 Silicone 1.2 >20 Superelastic alloy ≤150 6-10
[0048] In order to ensure the fatigue life of the material, a portion of elasticity, such as 0.5%, needs to be reserved to ensure that the material can withstand tens of thousands of bends without breaking. Therefore, if the shell of the ultra-thin high-flexibility heat spreader uses a metal foil with a thickness of 0.01mm to 0.25mm, when the bending radius is large, the ultra-thin high-flexibility heat spreader may be bent repeatedly without failure, but at this time the device has no strength and is easily deformed, and the yield rate is low. Once the bending radius becomes smaller than 2mm, the strain of the material quickly exceeds 2%, or even as high as 4%, which will cause plastic deformation of the material (ordinary metal and alloy materials). When bent repeatedly, the ultra-thin high-flexibility heat spreader will quickly crack and fail. Although polymer materials (such as silicone, etc.) have high elasticity, due to their non-dense molecular structure, when they are very thin, they have long been difficult to use as sealing materials for a long time due to reasons such as air permeability, thermal conductivity, high and low temperature impact resistance, and reliability of bending fatigue resistance, and the heat dissipation effect is not as good as that of metal materials.
[0049] Superelasticity refers to the phenomenon that a specimen produces a strain far greater than its elastic limit strain under the action of external force, but the strain can still recover automatically when unloading. That is, in the parent phase state, due to the effect of external stress, stress-induced martensitic phase transformation occurs, so that the alloy exhibits mechanical behavior different from that of ordinary materials, its elastic limit is much greater than that of ordinary materials, and it no longer obeys Hooke's law. Compared with shape memory properties, superelasticity has no thermal involvement. In short, superelasticity means that within a certain deformation range, stress does not increase with the increase of strain.
[0050] For example, the elastic deformation of superelastic alloys can reach 6-10% and the elastic modulus is less than or equal to 150Gpa; if superelastic alloys are used, the shell wall thickness of the ultra-thin high-flexibility heat spreader can be 0.01mm~0.25mm (preferably 0.1mm~0.2mm) to obtain good elastic bending deformation performance, and it can be ensured that under the bending state of R=2mm or above, the bending deformation is always in the elastic deformation zone; when the external force is removed, the deformation can be completely restored, which greatly extends the bending life and can meet the heat dissipation requirements at the rotating joints of electronic products.
[0051] The shell of the ultra-thin high-flexibility heat spreader in this embodiment includes a first side cover structure 11 and a second side cover structure 12 that are snapped together. They are usually fixedly connected by welding, preferably brazing, to ensure high reliability of multiple bending seals. A closed cavity is formed between the first side cover structure 11 and the second side cover structure 12. In order to improve the heat dissipation effect, the closed cavity is set as a negative pressure cavity with a vacuum degree of -2Pa. Of course, the vacuum degree of the closed cavity can also be adjusted according to the specific use environment and the type of liquid working medium. Among them, the cover surface of the first side cover structure 11 forms the evaporation side, and the cover surface of the second side cover structure 12 forms the condensation side. The evaporation side is bonded to the heat source through a thermal conductive adhesive.
[0052] In order to prevent the shell corresponding to the evaporation side and the shell corresponding to the condensation side from deforming during vacuuming, thereby affecting the airtightness of the closed cavity, a plurality of support structures 30 arranged at intervals are provided inside the closed cavity. Each support structure 30 is respectively supported between the evaporation side and the condensation side, and a steam channel is formed between two adjacent support structures 30.
[0053] In some embodiments, the support structure 30 and the shell on the evaporation side or the shell on the condensation side are integrally formed. Preferably, the support structure 30 and the shell on the evaporation side or the shell on the condensation side are integrally formed by stamping or etching.
[0054] Specifically, in the bent state, a bent portion 13 is formed in the housing portion between two adjacent support structures 30, and the distance between the two adjacent support structures 30 at the corresponding bent portion 13 gradually decreases from the condensation side to the evaporation side. In some other embodiments, in the bent state, the distance between the two adjacent support structures 30 located at the rotational joint of the electronic product remains constant.
[0055] In this embodiment, the overall thickness of the ultra-thin high-flexibility heat spreader is less than or equal to 1 mm, wherein the wick structure 20 is porous plastic, porous polymer, porous metal or multi-layer woven mesh, and the thickness of the wick structure 20 is less than or equal to 0.5 mm.
[0056] The heat dissipation function of the ultra-thin and highly flexible heat spreader is mainly achieved through the gas-liquid phase change of the working fluid. The heat dissipation process of the ultra-thin and highly flexible heat spreader includes four main steps: conduction, evaporation, convection, and condensation. The heat dissipation principle is as follows: the heat generated by the heat source enters the closed cavity through heat conduction on the evaporation side, and the liquid working fluid inside the wick structure 20 close to the heat source absorbs the heat and quickly vaporizes, taking away a large amount of heat at the same time; the steam inside the steam channel diffuses from the high-pressure area to the low-pressure area (i.e., the low-temperature area), and when the steam contacts the condensation side with a lower temperature, it will quickly condense into a liquid state and release heat energy; the working fluid condensed into a liquid state returns to the heat source under the action of the capillary force generated by the microstructure of the wick structure 20, thereby completing a heat conduction cycle and forming a two-way circulation system in which the working fluid gas and liquid phases coexist.
[0057] In this embodiment, the liquid absorbent core structure 20 includes a first liquid absorbent core portion 21 arranged on the inner side wall of the shell on the evaporation side, and a second liquid absorbent core portion 22 arranged on the inner side wall of the shell on the condensation side. A steam chamber is formed between the first liquid absorbent core portion 21 and the second liquid absorbent core portion 22, that is, the first liquid absorbent core portion 21 is arranged on the inner side wall of the first side cover structure 11, and the second side cover structure 12 is arranged on the inner side wall of the second side cover structure 12; one end of the support structure 30 is arranged on the shell on the evaporation side or the shell on the condensation side, and the first liquid absorbent core portion 21 and the second liquid absorbent core portion 22 are provided with avoidance openings for avoiding the support structure 30.
[0058] Specifically, the first absorbent core 21 is attached to the inner side wall of the shell on the evaporation side (the inner side wall of the first side cover structure 11), and the second absorbent core 22 is attached to the inner side wall of the shell on the condensation side (the inner side wall of the second side cover structure 12), that is, the first absorbent core 21 and the inner side wall of the shell on the evaporation side (the inner side wall of the first side cover structure 11) are split structures, and the second absorbent core 22 and the inner side wall of the shell on the condensation side (the inner side wall of the second side cover structure 12) are split structures. Usually, the first absorbent core 21 and the second absorbent core 22 respectively include a bonding plate body and an annular peripheral wall portion arranged at the peripheral edge of the bonding plate body, and the annular peripheral wall portion of the first absorbent core 21 and the annular peripheral wall portion of the second absorbent core 22 are connected together after bonding.
[0059] In some other embodiments, the first liquid absorbent core 21 and the shell on the evaporation side are integrally formed, and the second liquid absorbent core 22 and the shell on the condensation side are integrally formed. That is, the first liquid absorbent core 21 and the second liquid absorbent core 22 are formed by removing part of the shell, and the method of removing part of the shell is preferably wet etching or precision stamping.
[0060] In order to further increase the buffer strain, an elastic buffer energy absorption layer is provided on the outer wall of the shell, which can increase the elasticity and effectively avoid local excessive bending or dispersed stress. Usually, an elastic buffer energy absorption layer is provided on the outer wall of the shell corresponding to the condensation side and the evaporation side; preferably, PI, PP, PE and other materials with high elasticity, and the thickness of the elastic buffer energy absorption layer is less than or equal to 50um. In some embodiments, a groove structure can also be provided on the outer wall of the shell corresponding to the condensation side and the evaporation side, and at the same time, the effective thickness of the shell at the groove structure is not less than 10um.
[0061] In this embodiment, the superelastic foil is preferably made of a titanium-nickel alloy; the atomic percentage of titanium and nickel in the titanium-nickel alloy is greater than or equal to 40%, and the total atomic percentage of the remaining elements is less than or equal to 10%; and the total atomic percentage of all elements in the titanium-nickel alloy is 100%. The remaining elements include one or more of copper, iron, niobium and zirconium.
[0062] In some embodiments, the titanium-nickel alloy is preferably TiNi50 alloy, TiNiBb alloy or TiNi49Zr1 alloy.
[0063] In order to further illustrate the present technical solution, a number of experiments are described in detail below.
[0064] Test 1#:
[0065] 1) Material selection for ultra-thin and highly flexible vapor chamber
[0066] Shell: Thickness 0.1mm, TiNi50 alloy foil is selected, the material elastic limit is 6.8%, and the strength is 780MPa.
[0067] Support structure 30: support pillars with a diameter of 2 mm, a height of 0.2 mm and a spacing of 10 mm.
[0068] Liquid wick structure 20: 200 mesh braided copper mesh, thickness 0.2mm
[0069] Working fluid: Pure water is the working fluid, with a mass of 0.18g.
[0070] Internal air pressure: 0.3atm.
[0071] 2) Manufacturing of ultra-thin and highly flexible heat spreader
[0072] The woven copper mesh is placed in a vacuum-sealed chamber and sintered with the shell at 750°C for 7 hours in a mixed gas atmosphere of 5% hydrogen and 95% nitrogen. The shell is also diffusion welded together around the shell, leaving an injection opening.
[0073] 3) Liquid injection and vacuum sealing
[0074] Use a liquid injection machine to inject 0.18g of pure water into the closed cavity of the ultra-thin and highly flexible heat spreader, evacuate to 0.3atm, and seal the liquid injection port by argon arc welding.
[0075] 4) Finished products
[0076] The ultra-thin and highly flexible vapor chamber is aged at 120°C for 12 hours, tested for air tightness, and cut around to obtain the finished product of the set size.
[0077] 5) Testing
[0078] The power of the ultra-thin and highly flexible vapor chamber was tested according to the GB / T14812-2008 heat pipe heat transfer performance test method. It is stipulated that when the continuous input power increases, the temperature difference between the evaporation end and the condensation end of the ultra-thin and highly flexible vapor chamber is set to 3°C, which is the thermal power of the ultra-thin and highly flexible vapor chamber. The power of the ultra-thin and highly flexible vapor chamber was measured to be 3.3W. The ultra-thin and highly flexible vapor chamber was bent 10,000 times at a radius of R = 3mm, with a bending angle of 110°, and left to stand for 24 hours. The power was tested again and was 3.2W. It was bent 50,000 times at a bending angle of 110°, and left to stand for 24 hours. The power was tested again and was 3.1W.
[0079] Test 2#:
[0080] The design and manufacturing process of the ultra-thin and highly flexible heat sink are exactly the same as those in Experiment 1 and will not be described in detail here. In this experiment, the shell material is TiNi50 alloy foil with a thickness of 0.15 mm, an elastic limit of 8.2%, and a strength of 852 MPa.
[0081] The power of the ultra-thin and highly flexible vapor chamber was tested according to the GB / T14812-2008 heat pipe heat transfer performance test method, and the power of the ultra-thin and highly flexible vapor chamber was measured to be 3.1 W. The ultra-thin and highly flexible vapor chamber was bent 10,000 times at a radius of R = 3 mm, with a bending angle of 110°, and left to stand for 24 hours. The power was tested again to be 3.0 W. It was bent 50,000 times at a bending angle of 110°, and left to stand for 24 hours. The power was tested again to be 2.9 W.
[0082] Test #3:
[0083] The design and manufacturing process of the ultra-thin high-flexibility heat spreader are exactly the same as those in Experiment 1 and will not be described in detail here. In this experiment, the shell material is TiNi50 alloy foil with a thickness of 0.2 mm, an elastic limit of 8.2%, and a strength of 852 MPa.
[0084] The power of the ultra-thin and highly flexible vapor chamber was tested according to the GB / T14812-2008 heat pipe heat transfer performance test method, and the power of the ultra-thin and highly flexible vapor chamber was measured to be 2.9 W. The ultra-thin and highly flexible vapor chamber was bent 10,000 times at a radius of R = 3 mm, with a bending angle of 110°, and left to stand for 24 hours. The power was tested again and found to be 2.7 W. The ultra-thin and highly flexible vapor chamber was bent 50,000 times at a bending angle of 110°, and left to stand for 24 hours. The power was tested again and found to be 2.5 W.
[0085] Test 4#:
[0086] The design and manufacturing process of the ultra-thin high-flexibility heat spreader are exactly the same as those in Experiment 1 and will not be described in detail here. In this experiment, the shell material is TiNi49Zr1 alloy foil with a thickness of 0.1 mm, an elastic limit of 8.2%, and a strength of 852 MPa.
[0087] The power of the ultra-thin and highly flexible vapor chamber was tested according to the GB / T14812-2008 heat pipe heat transfer performance test method, and the power of the ultra-thin and highly flexible vapor chamber was measured to be 3.6 W. The ultra-thin and highly flexible vapor chamber was bent 10,000 times at a radius of R = 3 mm, with a bending angle of 110°, and left to stand for 24 hours. The power was tested again and found to be 3.6 W. It was bent 50,000 times at a bending angle of 110°, and left to stand for 24 hours. The power was tested again and found to be 3.5 W.
[0088] Test #5:
[0089] The design and manufacturing process of the ultra-thin and highly flexible heat spreader are exactly the same as those in Experiment 1, so we will not go into details here. In this experiment, the shell material is oxygen-free copper foil with a thickness of 0.1 mm, an elastic limit of 0.3%, and a strength of 85 MPa.
[0090] The power of the ultra-thin and highly flexible vapor chamber was tested according to the GB / T14812-2008 heat pipe heat transfer performance test method, and the power of the vapor chamber was measured to be 3.7W. The ultra-thin and highly flexible vapor chamber was bent 10,000 times at a radius of R = 3mm, with a bending angle of 110°, and left to stand for 24 hours. The ultra-thin and highly flexible vapor chamber shell cracked, the vacuum was broken, and the internal water flowed out. The power was tested to be 0.5W.
[0091] Test #6:
[0092] The design and manufacturing process of the ultra-thin high-flexibility heat spreader are exactly the same as those in Experiment 1 and will not be described in detail here. The material of this embodiment is stainless steel, with an elastic limit of 1.5% and a strength of 345 MPa.
[0093] The power of the ultra-thin high-flexibility vapor chamber was tested according to the GB / T14812-2008 heat pipe heat transfer performance test method, and the power of the ultra-thin high-flexibility vapor chamber was measured to be 3.2W. The ultra-thin high-flexibility vapor chamber was bent 10,000 times at a radius of R = 3mm, with a bending angle of 110°, and left to stand for 24 hours. The ultra-thin high-flexibility vapor chamber shell cracked and water flowed out. The power was tested to be 0.2W.
[0094] Table 3 is a comparison of the six test results
[0095]
[0096] In summary, the present invention can not only quickly conduct the heat generated by the heat source, but also, through experiments, it has been verified that the heat spreader used for conducting heat is always in the elastic deformation zone of the material when repeatedly bent, and the bending life can reach tens of thousands to hundreds of thousands of times, and it is not easy to fail due to repeated bending at a small angle. In other words, the ultra-thin and highly flexible heat spreader has a good heat dissipation effect and is not easy to fail due to repeated bending at a small angle, and has a long service life.
[0097] The present invention also discloses a pair of smart glasses, which include a glasses body, two temples respectively hinged to opposite sides of the glasses body, and the above-mentioned ultra-thin high-flexibility heat spreader. Specifically, since the main heat-generating electronic components of the mainboard and battery of the smart glasses are usually arranged inside the temples, and the internal space of the temples is relatively small, in order to avoid the excessive temperature of the temples affecting the user's wearing, one end of the ultra-thin high-flexibility heat spreader is arranged inside the temples and fits together with the heat-generating components inside the temples, and the other end is inserted into the glasses body.
[0098] Among them, two temple hinge ears are arranged at intervals at the ends of the temples near the main body of the glasses, and two main body hinge ears are arranged at intervals on the corresponding sides of the main body of the glasses, and the two temple hinge ears are located between the two main body hinge ears, and a main body avoidance space connected to the inside of the main body of the glasses is formed between the two main body hinge ears, and a temple avoidance space connected to the inside of the temple is formed between the two temple hinge ears. The ultra-thin high-flexibility heat spreader is connected between the temple and the main body of the glasses through the temple avoidance space and the main body avoidance space. One end of the ultra-thin high-flexibility heat spreader extends into the inside of the temple and is bonded to the heat-generating components through the thermal conductive adhesive, and the other end passes through the main body avoidance space and is inserted into the inside of the main body of the glasses, and is bonded to the shell of the main body of the glasses. The shape of the ultra-thin high-flexibility heat spreader can be processed into a rectangle according to the structural characteristics of the smart glasses and then bent into an L shape, or directly processed into an L shape, or directly adopts a rectangle, which is not limited here.
[0099] Of course, the ultra-thin and highly flexible heat spreader can also be directly set inside the temple, with the evaporation side attached to the heat-generating components and the condensation side attached to the outer wall of the temple away from the user's head. Its specific usage is not limited here.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An ultra-thin and highly flexible vapor chamber, characterized in that: include: A shell, wherein the shell is arranged to form a closed cavity, and opposite sides of the shell respectively form an evaporation side and a condensation side, and the shell is made of a superelastic foil with an elastic limit of 6% to 10% and an elastic modulus of less than or equal to 150 GPa, and the thickness of the superelastic foil is 10 um to 250 um; A wick structure connected between the evaporation side and the condensation side and capable of forming a reflux path between the evaporation side and the condensation side; And a liquid working medium is filled in the closed cavity and absorbed by the liquid wick structure, and the heat conducted to the evaporation side is conducted to the condensation side for heat dissipation by utilizing the heat dissipation principle of the gas-liquid two-phase change of the liquid working medium.
2. The ultra-thin high-flexibility vapor chamber according to claim 1, characterized in that: The superelastic foil is made of a titanium-nickel alloy, in which the atomic percentages of titanium and nickel are greater than or equal to 40%, and the total atomic percentages of the remaining elements are less than or equal to 10%; and the total atomic percentages of all elements in the titanium-nickel alloy are 100%.
3. The ultra-thin high-flexibility vapor chamber according to claim 2, characterized in that: The remaining elements include one or more of copper, iron, niobium and zirconium.
4. The ultra-thin high-flexibility vapor chamber according to claim 2, characterized in that: The titanium-nickel alloy is TiNi50 alloy, TiNiBb alloy or TiNi49Zr1 alloy.
5. The ultra-thin high-flexibility vapor chamber according to claim 1, characterized in that: The overall thickness of the ultra-thin high-flexibility vapor chamber is less than or equal to 1 mm.
6. The ultra-thin high-flexibility vapor chamber according to claim 1, characterized in that: The liquid absorbent core structure comprises a first liquid absorbent core portion arranged on the inner side wall of the shell on the evaporation side and a second liquid absorbent core portion arranged on the inner side wall of the shell on the condensation side, and a steam cavity is formed between the first liquid absorbent core portion and the second liquid absorbent core portion.
7. The ultra-thin high-flexibility vapor chamber according to claim 6, characterized in that: The first liquid absorbent core is attached to the inner wall of the shell on the evaporation side, and the second liquid absorbent core is attached to the inner wall of the shell on the condensation side. The first liquid absorbent core and the second liquid absorbent core are porous plastic, porous polymer, porous metal or multi-layer woven wire mesh; or, the first liquid absorbent core and the shell on the evaporation side are an integrally formed structure, and the second liquid absorbent core and the shell on the condensation side are an integrally formed structure.
8. The ultra-thin high-flexibility vapor chamber according to claim 1, characterized in that: An elastic buffer energy absorbing layer or a groove structure is provided on the condensation side and the evaporation side respectively.
9. The ultra-thin high-flexibility vapor chamber according to claim 1, characterized in that: The sealed chamber is configured as a negative pressure chamber.
10. The ultra-thin high-flexibility vapor chamber according to claim 1, characterized in that: The shell includes a first side cover structure and a second side cover structure that are snapped together, and the closed cavity is enclosed between the first side cover structure and the second side cover structure. The cover surface of the first side cover structure forms the condensation side, and the cover surface of the second side cover structure forms the evaporation side.
11. The ultra-thin high-flexibility vapor chamber according to any one of claims 1 to 10, characterized in that: The ultra-thin high-flexibility vapor chamber further includes a plurality of support structures spaced apart inside the closed cavity, each of the support structures being supported between the evaporation side and the condensation side.
12. The ultra-thin high-flexibility vapor chamber according to claim 11, characterized in that: In the bent state, a bent portion is formed in the shell portion between two adjacent support structures, and the distance between the two adjacent support structures corresponding to the bent portion gradually decreases from the condensation side to the evaporation side.
13. A smart glasses, characterized in that: The invention comprises the ultra-thin high-flexibility heat spreader as described in any one of claims 1 to 12.